Functional foods and dietary supplements : processing effects and health benefits - Ahmad, Imran, 1974-; Anal, Anil (Wiley-Blackwell, 2014)
This book highlights the effects of food processing on the active ingredients of a wide range of functional food materials, with a particular focus on foods of Asian origin. Asian foods, particularly herbs, are becoming increasingly accepted and demanded globally, with many Western consumers starting to recognize and seek out their health-giving properties. This book focuses on the extraction of ingredients which from materials which in the West are seen as "alternative"--Such as flour from soybeans instead of wheat, or bran and starch from rice - but which have long histories in